Application of Modern Management Functions in Corporate Governance and Organizational Management Processes - Prasetio, Bagas (Sahabat Publikasi, 2025)
In the era of rapid digitalization and global economic transformation, modern management has evolved from a purely administrative function into a strategic imperative for organizational success. This study examines the application of modern management functions—planning, organizing, directing, and controlling in corporate governance and organizational management processes. Through a comprehensive analysis of contemporary management practices, this research highlights how organizations must shift from traditional, linear approaches to more adaptive, technology-driven, and integrated systems. The study employs PT Gojek Indonesia as a primary case study to illustrate the practical implementation of modern management functions, including strategic planning utilizing AI and predictive analytics, flexible organizational structures with cross-functional teams, transformational leadership styles, and real-time control systems based on ERP and KPIs. The research also presents a critical analysis comparing Gojek's approach with its competitor Grab, revealing both strengths and inherent risks such as employee resistance to technology adoption, high implementation costs, ambiguity in flexible structures, and over-reliance on digital systems. Furthermore, this study contextualizes modern management within Indonesia's unique landscape, addressing challenges such as uneven technological infrastructure, hierarchical organizational culture, and regulatory complexities, while also recognizing significant opportunities in the large domestic market and government support for digital economy initiatives. The integration of Environmental, Social, and Governance (ESG) principles emerges as a crucial component of sustainable modern management. The findings demonstrate that successful modern management requires not only the adoption of advanced technologies and innovative practices but also careful change management, investment in human capital, balance between flexibility and clarity, and alignment with ethical values and sustainability principles to achieve meaningful long-term organizational growth.